Pseudophanacis Subgen. n. - новый подрод рода Phanacis Forster (Hymenoptera, Cynipoidea) с описанием новых видов - Дьякончук, Л.А. (Вестник зоологии, 1981)
The paper presents a description of the new subgenus Pseudophanacis subgen. n. of the genus Phanacis Forster
anda description of the type species Pseudophanacis culmicola sp. n. isolated from the CentaureaadpressaL e d e b .stalks.The new subgenus. is characterized by an open radial cell on the fore wing; the 2nd and the last segments of the hind leg are equal in length; cigar-like shape of the abdomen; elongated stalk on the egg.Besides, twonew species of this subgenus are alsodescribed: Pseudophanacis stepicolasp. n. isolatedfrom stalksof the Centaurea adpressaX C. orientalis hybrid and Pseudophanacis orientalis sp. n. isolated from stalks of C. orientalis L.